2022
DOI: 10.1089/jpm.2020.0715
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Index for Predicting Survival of Patients Undergoing Radiation Therapy for Spine Metastasis Using Recursive Partitioning Analysis

Abstract: Background: Physicians' estimate of life expectancy in patients with spine metastasis frequently impacts treatment decisions regarding surgery, radiation techniques, dose, and fractionation. Objective: We aimed to identify predictors of survival and generate a stratification schema that could guide clinical decision making. Materials and Methods: We identified 269 patients who have undergone surgery and/or radiation for spine metastasis from 2002 to 2013 at an academic medical institution in the United States.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was suggested based on their limited analysis and noted survival among the risk groups that the Combs Prognostic Score should be used in clinical decision making and patient stratification. We observed that in select situations, such as recurrent disease, brain metastases, and spinal cord compression, there is some evidence to guide who may be suitable for retreatment or SBRT based on their life expectancy ( [11,19,22,28,31,32,34,35,38,39,43,44] and [12] (p. 20)). Patients with a longer predicted survival are generally more suitable for longer courses of PRT, as they are more likely to complete their treatment [45].…”
Section: Resultsmentioning
confidence: 93%
“…It was suggested based on their limited analysis and noted survival among the risk groups that the Combs Prognostic Score should be used in clinical decision making and patient stratification. We observed that in select situations, such as recurrent disease, brain metastases, and spinal cord compression, there is some evidence to guide who may be suitable for retreatment or SBRT based on their life expectancy ( [11,19,22,28,31,32,34,35,38,39,43,44] and [12] (p. 20)). Patients with a longer predicted survival are generally more suitable for longer courses of PRT, as they are more likely to complete their treatment [45].…”
Section: Resultsmentioning
confidence: 93%